THE EFFECTS OF GREEN CULTURE AND EMPLOYEE MOTIVATION ON GREEN WORKPLACE PRACTICE IN THE FOOD AND BEVERAGE INDUSTRY IN INDONESIA - Rosyanti, Daisy Marthina; Khoirotunnisa, Fani; Dewanti, Mentari Clara (Jurnal Aplikasi Manajemen, 2023)
The issue of green business practices has become an exciting topic to study in recent years. To achieve the SDGs, applying Green Human Resources Management in green business practices is an essential aspect because of its role as a key factor in the company's success. Given that the Food and Beverage industry is one of the industries with the most millennial generation employees, the support for millennial teamwork on green business practices is urgent in this study, "Are millennials involved in green practices." This study aimed to measure Green Workplace Practices among millennial employees through the relationship between green motivation (intrinsic and extrinsic) and green culture in the F&B industry in Indonesia. Data collection was done through a questionnaire. The sample in this study was 67 respondents processed using the purposive sampling method and structural equation modeling technique based on partial least squares. This study revealed that green motivation research can significantly influence green workplace practices and that green organizational culture plays a role in moderating the relationship between green motivation and green workplace practices. This research has significant implications for managers to see positive consequences when organizations adopt green practices. When organizations agree to reconstruct a green culture, they are not only doing their moral responsibility to society and the environment but investing in business sustainability in the future. The researcher realized there are limitations in the research, both in terms of time and quantity of data on millennial employees in the Food and Beverage industry that have not been fully explored optimally. Considering that there are not many studies on similar themes and research findings can be used as a foundation for future research.